PHENOMENON UNDERSTANDING OF NATURAL DISASTERS THROUGH FIELD STUDY METHODS IN GEOGRAPHY PHYSICAL GEOGRAPHY AS unifying - Syaiful - Khafid (Universitas Pendidikan Ganesha, 2016)
The aim of writing this article is to know the learning of physical geography by field study in understanding natural disaster. The core components of physical geography in unifying geography are space, lacation, environment, and map having the dimension of time, process, openness, and scale. The learning of physical geography is stressed on the phenomena of natural disaster which is caused by human activities, such as the overflow of hot mud, landslide, and flood in the hope that the learners have sufficient knowledge of physical geography in responding, understanding, and preventing natural disaster which occur in the region or in the neighbouring region. This can be achieved when geography teachers learn the material of physical geography by facilitating the learners to be active in conducting field study to understand the phenomena of the occuring natural disaster. Keywords: physical geography, unifying geography, field study, natural disaster.